The Yamaha ClassBand approach in the Music classroom. An experience in Secondary Education in Madrid - González Serra, Alfonso; León Barranco, Luis Ponce de (Pulso. Revista de educación, 2017)
Yamaha ClassBand is a novel teaching approach in Spain by which students learn music through instrumental performance, all class members be-coming a band. Our aim was to study how this music teaching method was implemented in a specific high school in Madrid, IES Las Rozas 1. Some of the aims of the method are to foster significant learning, intrinsic motivation and coop-erative learning. We analised the particularities of the approach, the phases it entails, and some of the challenges that the teachers face. One of the risks when adopting the method is dedicating ex-clusive attention to performing issues, or making students depend on sight-fingering associations without a sufficient participation of the musical ear. We also reflect suggestions for improvement expressed by students that experimented the ClassBand method. The demand for more weekly class hours allocated to the subject of Music was the most frequent suggestion among these stu-dents
Keywords: Yamaha ClassBand; Music education; Performing; Band; High school